2021
DOI: 10.3390/en14144354
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Microstructured Charcoal Additive on ANFO’s Properties

Abstract: The verification of the blasting parameters of Ammonium Nitrate Fuel Oil (ANFO) with the addition of microstructured charcoal (MC) produced by destructive wood distillation was performed. Additional investigation of specific surface and pore distribution by the nitrogen adsorption of the two granulations of MC was also carried out. High-resolution scanning electron microscopy was used for morphology evaluation and revealed smoothening of the initially developed external surface of carbon with intensive milling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…In our recent work [ 47 ], we reported that the maximum of DSC peak responsible for the decomposition of AN can depend on both the size of the microstructured charcoal (MC) grains and the chemical composition of the prepared samples. Generally, higher MC content and smaller MC grains lowered ANFO decomposition temperature (from 292 to 272 °C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent work [ 47 ], we reported that the maximum of DSC peak responsible for the decomposition of AN can depend on both the size of the microstructured charcoal (MC) grains and the chemical composition of the prepared samples. Generally, higher MC content and smaller MC grains lowered ANFO decomposition temperature (from 292 to 272 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Post-blast fumes analysis was conducted according to the procedure described in [ 44 ], which was based on regulations reported in [ 45 ]. The description of blasting tests has also been reported in our previous works [ 41 , 46 , 47 ]. In each experiment, 600 g of non-ideal ANFO charge was placed inside the steel mortar locked in the blasting chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The rates of heat energy release are in this case significantly higher than for the pure components of the mixture alone. The charcoal addition as an ANFO component was investigated in [25,26]. The effect of chemically bound carbon on the properties of thermal decomposition of AN was investigated in [27].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of the results of the analysis is conducted based on the fact that the concentrations of carbon monoxide (CO) and carbon dioxide (CO 2 ) is constant after the initial mixing period (homogenization of the post-detonation gas mixture). Due to the occurrence of consecutive reactions between the detonation products, the initial concentrations of nitrogen oxides (NO, NO X and NO 2 ) are determined by plotting a dependence of the concentration of each substance over time that has elapsed since detonation and extrapolating the experimental curve to the moment of detonation [ 30 ]. The initial concentrations of post-detonation gases ( C G ) are used to calculate the quantity of each gas ( Q G ) at normal conditions (273 K, 760 mm Hg ) via Equation ( 2 ): where: p 1 —measured pressure in the chamber after detonation [mm Hg ] T 1 —measured temperature in the chamber after detonation [K] V ch —volume of the experimental chamber [dm 3 ] m —mass of the detonated explosive sample [kg] …”
Section: Materials and Methodsmentioning
confidence: 99%